E-084 Long-Term Clinical Outcomes in Patients with Acute Ischemic Strokes Treated with Mechanical Thrombectomy who had Moderate or Moderate Severe Disability at 90 Days. (29th July 2016) - Delgado Almandoz, J; Hochsprung, S; Kayan, Y; Fease, J; Scholz, J; Milner, A; Roohani, P; Mulder, M; Hehr, T; Tarrel, R; Chappuis, D; Young, M
Abstract : Background and purpose: Long-term clinical outcomes in patients with acute ischemic stroke (AIS) treated with mechanical thrombectomy (MT) are not well understood. This study aims to determine long-term clinical outcomes in a consecutive cohort of patients with AIS treated with MT who had moderate or moderate severe disability at 90 day follow-up. Methods: Our prospectively-maintained institutional neurointerventional database was queried to identify all patients with AIS treated with MT at our institution from July 1st, 2011 until September 30th, 2015 who had moderate (modified Rankin Scale, mRS, 3) or moderate severe (mRS 4) disability at the time of the 90 day follow-up. At least 6 months after stroke onset, medical records were reviewed and/or phone interviews were conducted by a nurse certified in the mRS and independent of the MT procedure to determine the mRS at the time of last clinical contact. Baseline clinical and radiological characteristics were also obtained. Results: Forty patients met the study's inclusion criteria, comprising 29% of patients treated with MT at our institution during the study period. Twenty patients were male (50%) and 20 female (50%). At presentation, 14 patients had a history of atrial fibrillation (35%), 28 hypertension (70%) and 13 diabetes mellitus (33%). Mean age was 69.8 years. Mean admission NIHSS was 18.2. Twenty-five patients received intravenous tissue plasminogen activator (63%). Thrombus location was M1 segment in 18 patients (45%), internal carotid artery terminus in 14 patients (35%), basilar artery in 4 patients (10%) and M2/M3 segment in 4 patients (10%). Discharge disposition was acute inpatient rehabilitation in 26 patients (65%) and skilled nursing facility in 14 patients (35%). At the time of the 90 day follow-up visit, 18 patients had an mRS of 3 (45%) and 22 had an mRS of 4 (55%). All patients continued to undergo outpatient rehabilitation treatment after the 90 day follow-up visit. Mean time to long-term clinical follow-up was 21.5 months after stroke onset (median 18.8 months, range 6–49 months). The table illustrates the clinical outcomes at the time of long-term follow-up. Between the 90 day and long-term follow-ups, 12 patients (30%) had a reduction of at least 1 point in the mRS, whereas 10 patients (25%) had an increase of at least 1 point in the mRS. At the time of long-term follow-up, 23 patients lived at home (58%), 3 in an assisted living facility (8%), 6 in a skilled nursing facility (15%) and 8 were deceased (20%). Four patients had experienced a recurrent AIS (10%) by the time of long-term follow-up. Conclusion: Among patients with AIS treated with MT who had moderate or moderate severe disability at 90 days, a considerable minority (30%) demonstrated a reduction in long-term disability with continued outpatient rehabilitation. Disclosures: J. Delgado Almandoz: 2; C; Medtronic Neurovascular, Penumbra, Inc. S. Hochsprung: None. Y. Kayan: 2; C; Medtronic Neurovascular, Penumbra, Inc. J. Fease: None. J. Scholz: None. A. Milner: None. P. Roohani: None. M. Mulder: None. T. Hehr: None. R. Tarrel: None. D. Chappuis: None. M. Young: None.